Macrophage Migration Inhibitory Factor (MIF) and Thyroid Hormone Alterations in Antineutrophil Cytoplasmic Antibody (ANCA)-Associated Vasculitis (AAV) - Mårten Wendt; Ola Börjesson; Aune Avik; Johan Bratt; Björn Anderstam; Abdul R. Qureshi; Edmund J. Miller; Iva Gunnarsson; Annette Bruchfeld (BMC, 2013)
Abstract Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine known to be released from lymphocytes, macrophages and endothelial cells and also in animal models shown to be inducible with glucocorticoids (GC). In contrast, thyroxine seems to antagonize MIF activity. To investigate whether MIF is increased in active antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and possible correlations with GC dosing and thyroid hormone levels, 27 consecutive patients with active AAV were studied and followed prospectively. Disease activity was assessed using Birmingham Vasculitis Activity Score 2003 (BVAS) at baseline and at follow-up at 3 and 6 months, along with MIF, thyroid hormones free triiodothyronine (fT3) and free thyroxine (fT4), C-reactive protein (CRP) and creatinine. MIF was elevated significantly at baseline compared with follow-up at 3 and 6 months (8,618 pg/mL versus 5,696 and 6,212 respectively; P < 0.002) but did not correlate to CRP GC dose, creatinine or organ involvement. fT3 was depressed significantly at baseline compared with follow-up (1.99 pg/mL versus 2.31 and 2.67 respectively; P = 0.01) and correlated inversely to the BVAS score at baseline. We found a significant correlation between the MIF/fT4 ratio at baseline versus MIF/fT4 ratio at 6 months (p = 0.52, P < 0.005) and a trend between the baseline MIF/fT3 ratio versus MIF/fT3 ratio at 6 months (ρ = 0.39, P = 0.05). These results suggest a possible role for MIF and thyroid status in AAV. Further studies could reveal whether the association between AAV and thyroid hormone levels in the context of elevated MIF may present a link as well as a target of treatment.